2013
DOI: 10.1364/ol.38.004656
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid single quantum well InP/Si nanobeam lasers for silicon photonics

Abstract: We report on a hybrid InP/Si photonic crystal nanobeam laser emitting at 1578 nm with a low threshold power of ∼14.7 μW. Laser gain is provided from a single InAsP quantum well embedded in a 155 nm InP layer bonded on a standard silicon-on-insulator wafer. This miniaturized nanolaser, with an extremely small modal volume of 0.375λ∕n 3 , is a promising and efficient light source for silicon photonics. However, the capability of generating light on silicon has been one of the daunting problems to overcome owing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…We adopt a one-dimensional (1D) photonic crystal cavity, which can achieve a high quality ( Q ) factor comparable with the two-dimensional (2D) counterpart, , while requiring a much smaller footprint and number of nanowires. The schematic illustration of our nanowire array laser is shown in Figure a.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We adopt a one-dimensional (1D) photonic crystal cavity, which can achieve a high quality ( Q ) factor comparable with the two-dimensional (2D) counterpart, , while requiring a much smaller footprint and number of nanowires. The schematic illustration of our nanowire array laser is shown in Figure a.…”
mentioning
confidence: 99%
“…Advancing from the lasing demonstration of nanowire array cavities formed on planar SOI substrates, we also demonstrate SOI waveguide-coupled nanowire array lasers integrated on silicon mesas, which supports the compatibility of the proposed lasers with PICs. We adopt a one-dimensional (1D) photonic crystal cavity, which can achieve a high quality (Q) factor comparable with the two-dimensional (2D) counterpart, 19,20 while requiring a much smaller footprint and number of nanowires. The schematic illustration of our nanowire array laser is shown in Figure 1a.…”
mentioning
confidence: 99%
“…Indeed, there have recently been several efforts to integrate III-V quantum well (QW) PC lasers on Si-chips [12][13][14][15][16][17][18]; various wafer bonding techniques such as molecular bonding [12,14,18], adhesive bonding [15][16][17], and metallic dry bonding [13] have been proposed and employed to bond the III-V QW material onto Si substrate prior to the fabrication of PC laser structures. Among these techniques, the adhesive bonding method is most widely used due to the fact that it does not have stringent interface requirements in contrast to the other bonding processes.…”
Section: Introductionmentioning
confidence: 99%
“…For the past decade, several research groups have demonstrated essential building blocks to process optical signals, for example: efficient and broadband input/output coupling systems from optical fibers to optical waveguides [3], high-speed electro-optic modulators [4][5][6], chip-scale ultrafast pulse compressor [7], tunable filters [8,9], polarization-independent devices [10], heterogeneous integration on silicon-on-insulator (SOI) to produce light sources and photodetectors [11][12][13][14][15][16][17][18][19], as well as unidirectional [20] and nonreciprocal devices [21,22], amongst others.…”
Section: Introductionmentioning
confidence: 99%